Cultivo de Physalis peruviana L. em sistema hidrop?nico com doses de f?sforo - Santos, Fl?vio Soares dos (2022)
Belonging to the Solanaceae family, Physalis peruviana L. is native to the Andes and adjacent areas, and is primarily recognized for its fruits, medicinal and pharmaceutical uses, and nutritional content. Its cultivation typically occurs in higher altitude areas with mild temperatures, which favor its growth and development. However, in terms of fertilization, more legitimate information is needed regarding its nutritional requirements, especially concerning essential macronutrients, specifically phosphorus, which is the most used nutrient in fertilization recommendations. This is because a large part of Brazilian soils does not naturally provide phosphorus, as it is complexed in the soil, reducing its availability for plant absorption. Therefore, the objective of this study was to evaluate different doses of phosphorus in the hydroponic cultivation of P. peruviana. The experiment was conducted at the Forest Garden of the State University of Feira de Santana, in a greenhouse, using a completely randomized design in hydroponic cultivation, with five phosphorus doses (0.0; 15.5; 31.0; 46.5 and 62.0 mg L-1 of P) being evaluated. After fifty-four days of cultivation, morphological aspects were analyzed: plant height and stem diameter, number of branches and leaves, leaf area, dry mass of leaves, shoot, and total dry mass; and biochemical aspects: chlorophyll (a), (b), and carotenoids, determination of phosphorus in leaves, stems, and roots. The phosphorus doses had a significant effect on the morphoagronomic characteristics, showing that P directly influences the growth and development of P. peruviana L. plants.